Dialectology at Vilnius University - Judžentytė-Šinkūnienė, Gintarė; Kardelis, Vytautas (Lietuvių kalba, 2024)
The paper aims to review the history of dialectology at Vilnius University since the establishment of the Department of the Lithuanian Language in 1940. To achieve this, we have set the following objectives: 1) to present the teaching of dialectology, 2) to review the dialect material collection, and 3) to examine existing research. Descriptive, analytical, and evaluative methods are applied in the study.The beginning of dialectological research is associated with the name of Antanas Salys. The works of Aleksas Girdenis and Zigmas Zinkevičius are also discussed in the paper, as well as the teaching of the dialectology subject, methods of collecting dialectological material and directions of dialectological research. The paper distinguishes the paradigms of traditional, structural, and new dialectology dialectology, and examines their methodological similarities and differences.The most important conclusions and summaries of the paper are fundamentally related to dialectological paradigms: in more than eighty years since the first dialectology subject taught at Vilnius University, the understanding of dialectology has changed. The stage of traditional dialectology at the University was extremely important, as it produced the most fundamental works that are still used today. The structural dialectology paradigm and Prof. Girdenis Dialectology School that trained a large group of productively working Lithuanian dialectologists has flourished over the years. Currently, the new paradigm of dialectology is making its way, offering new theoretical and methodological approaches to the study of dialects.
Keywords: Vilnius University; dialectology; teaching dialectology; dialectal material; research in dialectology